ANALISA DISTRIBUSI KEKERASAN KOMPONEN MOVABLE PULLEY DRIVEN (MPDN) PADA TRANSMISI KENDARAAN - Irwan Suriaman; Muhammad Al Makki; Jatira Jatira; Choirul Anwar (Jurnal Rekayasa Mesin, 2023)
Transmission on the vehicle is very important component to ensure maximum power transfer from the engine to the wheels. The speed of four-wheeled vehicles is influenced by the transmission system used. Pulley is the component of continuous variable transmission (CVT) which is currently widely used in the automotive industry. The CVT transmission is type of automatic transmission withÂ  gearshift process that does not use gears, but uses pulley. The pulley is made of stainless steel. For CVT transmission there are two pulleys, both of which are called driven pulleys. The CVT transmission shift operation is controlled electronically from the computer to drive the two pulleys. These two pulleys can move to the right or to the left, respectively, so that the width of the two pulleys can change to narrow or widen. The drive pulley moves away so the belt will move inward and the same time the driven pulley will narrow so the belt will move further out. The pulley diameter becomes the gear ratio in a CVT transmission. In the CVT transmission process there will be friction between the two surfaces of the pulley and the belt, therefore it is necessary to measure the hardness of the material from the pulley to ensure the vehicle's transmission capability. In this study, the hardness of the pulley material was measured using a Vickers machine according to the ASTM 6507 standard with a given load of 0.3 kg. The measurement results obtained an average value of hardness Vickers (HV) for the pulley material of 473.Â